The Accuracy of Relative Strength Index (RSI) Indicator in Forecasting Foreign Exchange Price Movement - Yulia Rossa Indah; Luh Putu Mahyuni (Politeknik Negeri Bengkalis, 2022)
This study aims to measure the accuracy of the Relative Strength Index (RSI) Indicator in predicting the direction of foreign exchange (forex) price movements. To achieve the research objectives, six foreign exchange currencies that fall into the major pair category were determined as samples. RSI data is collected from the Foreign Exchange Market which can be accessed via tradingview.com during the research period, January – September 2021. The data is analyzed using SPSS software with the Mann Whitney U Test which can prove statistically whether there is a significant difference between the predictions of forex price movements with the reality price movement. Thus, this study provides evidence of the accuracy of the Relative Strength Index (RSI) Indicator in predicting the direction of forex price movements. The findings of this study can be a reference for practitioners such as forex traders or business people who deal with foreign currencies in choosing technical analysis methods that can help make the right decisions.